2014
DOI: 10.1007/s00425-014-2189-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution and transcriptional regulation of the oilseed rape proline dehydrogenase genes suggest distinct roles of proline catabolism during development

Abstract: Six BnaProDH1 and two BnaProDH2 genes were identified in Brassica napus genome. The BnaProDH1 genes are mainly expressed in pollen and roots' organs while BnaProDH2 gene expression is associated with leaf vascular tissues at senescence. Proline dehydrogenase (ProDH) catalyzes the first step in the catabolism of proline. The ProDH gene family in oilseed rape (Brassica napus) was characterized and compared to other Brassicaceae ProDH sequences to establish the phylogenetic relationships between genes. Six BnaPro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…The degradation of Pro (Fig. 6, pathway VI) also appears as a central pathway releasing Glu and reducing equivalents; therefore, it is advantageous in highly energy-demanding developmental processes such as leaf senescence (Faes et al, 2015;Zhang and Becker, 2015). Here, we observed that the increase of transcript abundance of the two Arabidopsis Columbia-0 Pro dehydrogenases during senescence is similar.…”
Section: Mitochondria Orchestrate Senescence-associated Catabolism Tomentioning
confidence: 54%
“…The degradation of Pro (Fig. 6, pathway VI) also appears as a central pathway releasing Glu and reducing equivalents; therefore, it is advantageous in highly energy-demanding developmental processes such as leaf senescence (Faes et al, 2015;Zhang and Becker, 2015). Here, we observed that the increase of transcript abundance of the two Arabidopsis Columbia-0 Pro dehydrogenases during senescence is similar.…”
Section: Mitochondria Orchestrate Senescence-associated Catabolism Tomentioning
confidence: 54%
“…Another family was not affected by the N nutrition level but showed higher expression in stems than in leaves. Faes et al (2015) also demonstrated the differential expression of two subgroups of genes in the proline dehydrogenase gene family in rapeseed. These genes, ProDH1 and ProDH2, control proline catabolism, which is suspected to play a role in the remobilization of N from old to young leaves.…”
Section: Genetic Control Of Traits Related To Nitrogen Utilization Efmentioning
confidence: 88%
“…One observation is that during natural leaf aging proline catabolism appears to be upregulated via increased expression of PRODH2 and P5CDH . In Arabidopsis thaliana and Brassica napus (rapeseed), PRODH2 expression was strongly induced in the course of natural leaf aging ( Funck et al, 2010 ; Faes et al, 2015 ), whereas PRODH1 expression was moderately upregulated ( Funck et al, 2010 ). P5CDH expression was also reported to increase in older leaves of Arabidopsis ( Deuschle et al, 2004 ).…”
Section: Proline In Leaf Senescence: Upregulation Of Proline Catabolimentioning
confidence: 99%